2002
DOI: 10.1038/sj.jhh.1001395
|View full text |Cite|
|
Sign up to set email alerts
|

Antihypertensive efficacy of olmesartan compared with other antihypertensive drugs

Abstract: The therapeutic profile of olmesartan medoxomil, which is a recently developed angiotensin II (A II)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
1
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 13 publications
1
51
1
2
Order By: Relevance
“…5 The present study sought to assess the antihypertensive efficacy and goal BP attainment rate with the recommended starting dose of olmesartan medoxomil, compared with that of the most widely prescribed antihypertensive agent, amlodipine. Although other ARBs have been compared with amlodipine in clinical trials, [20][21][22][23] the studies focused primarily on the absolute reduction in BP between the two agents and not on their ability to achieve a specific BP goal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 The present study sought to assess the antihypertensive efficacy and goal BP attainment rate with the recommended starting dose of olmesartan medoxomil, compared with that of the most widely prescribed antihypertensive agent, amlodipine. Although other ARBs have been compared with amlodipine in clinical trials, [20][21][22][23] the studies focused primarily on the absolute reduction in BP between the two agents and not on their ability to achieve a specific BP goal.…”
Section: Discussionmentioning
confidence: 99%
“…4 Olmesartan medoxomil has exhibited antihypertensive efficacy that compares favourably with that of atenolol, captopril, felodipine, and the ARBs losartan potassium (losartan), valsartan, and irbesartan in randomized, doubleblind, head-to-head comparative trials. [5][6][7] The present study was conducted to compare the efficacy and safety of the starting doses of olmesartan medoxomil and amlodipine besylate (amlodipine), currently the most widely prescribed antihypertensive agent, in patients with mild-to-moderate hyper-tension, as well as to compare the BP control rates achieved by olmesartan medoxomil and amlodipine. These data are useful in order to provide clinicians with information on alternative therapeutic regimens in the treatment of hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…Among ARBs, olmesartan selectively inhibits Ang II binding to Ang II subtype 1 (AT1) receptors with high potency and affords satisfactory BP control in monotherapy with a good tolerability profile (20)(21)(22)(23). Its combination with hydrochlorothiazide (HCTZ) has been shown to provide better 24-h BP control than monotherapy in patients with mild-to-moderate as well as in those with severe hypertension (24,25).…”
Section: Introductionmentioning
confidence: 99%
“…In another study by Stumpe et al, 7 381 patients with MSDBP 100-120 mm Hg were randomised to olmesartan medoxomil 20 mg/day, or felodipine 5 mg/day. Both drugs lowered the MSDBP/MSSBP to the same degree.…”
Section: Active Comparative Studiesmentioning
confidence: 99%
“…In several randomised placebo-controlled studies, olmesartan medoxomil has demonstrated significant antihypertensive effects compared to placebo. 1,2 In other comparative studies, olmesartan medoxomil showed similar blood pressure (BP) lowering efficacy with angiotensin converting enzyme (ACE) inhibitors, calcium channel blockers, b-blockers and diuretics, [3][4][5][6][7][8][9] but superior antihypertensive potency against other ARBs given in equivalent starting doses. [10][11][12][13] In other studies, olmesartan medoxomil given in the highest recommended daily doses, its antihypertensive effect was similar to other ARBs.…”
Section: Introductionmentioning
confidence: 98%